Lost in a Story, Detached from the Words. Issue 7 (9th August 2021) - Eekhof, Lynn S.; Kuijpers, Moniek M.; Faber, Myrthe; Gao, Xin; Mak, Marloes; van den Hoven, Emiel; Willems, Roel M.
ABSTRACT: This article explores the relationship between low- and high-level aspects of reading by studying the interplay between word processing, as measured with eye tracking, and narrative absorption and liking, as measured with questionnaires. Specifically, we focused on how individual differences in sensitivity to lexical word characteristics—measured as the effect of these characteristics on gaze duration—were related to narrative absorption and liking. By reanalyzing a large data set consisting of three previous eye-tracking experiments in which subjects ( N = 171) read literary short stories, we replicated the well-established finding that word length, lemma frequency, position in sentence, age of acquisition, and orthographic neighborhood size of words influenced gaze duration. More importantly, we found that individual differences in the degree of sensitivity to three of these word characteristics, i.e., word length, lemma frequency, and age of acquisition, were negatively related to print exposure and to a lesser degree to narrative absorption and liking. Even though the underlying mechanisms of this relationship are still unclear, we believe the current findings underline the need to map out the interplay between, on the one hand, the technical and, on the other hand, the subjective processes of reading by studying reading behavior in more natural settings.